Sistema de gestión de mantenimiento basado en el riesgo para incrementar la confiabilidad de la maquinaria pesada de la empresa Chancadora del Norte S.A.C. - Montenegro Leyva, Gary Wlber (2018)
The use of the Risk-based Maintenance methodology contemplates not only the study of the equipment as such, but also the subsystems that comprise it and the interaction with the physical environment that surrounds it. In this thesis we first made an adequate identification of the problems that make it difficult for us to maximize the function of the heavy machinery of the company CHANCADORA DEL NORTE SAC, whose purpose is to optimize the maintenance management of the same, in order to obtain greater operational and mechanical availability, for the operations it carries out in its operations in mining companies in the Piura Region. When applying this proposal, significant savings would be obtained, which will be progressively reflected in the coming years. The results achieved are:  We were able to establish the indicators to ensure adequate maintenance management and ensure the operational availability of the company's heavy machinery.  We established improvement strategies in the maintenance area of these equipment.